An N-terminal domain of Dbf4p mediates interaction with both origin recognition complex (ORC) and Rad53p and can deregulate late origin firing - Duncker, Bernard P. (National Academy of Sciences, 2002)
The Dbf4/Cdc7 kinase acts at the level of individual origins to promote the initiation of DNA replication. We demonstrate through both immunoprecipitation and two-hybrid assays that a domain comprising the first 296 aa of Dbf4p interacts with Orc2p and Orc3p subunits of the origin recognition complex (ORC). Given that the activation of Rad53 kinase in response to the DNA replication checkpoint leads to the release of Dbf4p from an ORC-containing chromatin fraction, we also examined interaction between Dbf4p and Rad53p. This same domain of Dbf4p binds specifically to the forkhead homology-associated (FHA) domains of Rad53p. Cell cycle arrest in G(2)/M, provoked by the overexpression of the Dbf4 domain, is suppressed in a rad53 mutant. Moreover, its overexpression perturbs the regulation of late, but not early, origin firing in wild-type cells after treatment with hydroxyurea.